PEMBERDAYAAN INDIVIDU DENGAN CEREBRAL PALSY MELALUI PARTISIPASI PARA SPORT DI TOKYO JEPANG - Kholida Nabila; Suryo Saputra Perdana (Universitas Muhammadiyah Surakarta, 2025)
This community service program aims to enhance understanding and participation of individuals with Cerebral Palsy (CP) in adaptive sports by utilizing the BocciaGuard application as a classification support tool. The main issue faced by the partners is the limited screening and classification methods for CP athletes, which are still manually performed, leading to potential inaccuracies and unfair competition. The program implementation included scientific dissemination, interactive discussions, application training, and functional data-based classification simulations. Activities were conducted online and offline, involving physiotherapy students, academics, and practitioners from Indonesia and Japan. The results showed increased participants’ understanding of technology-based classification, improved skills in using the BocciaGuard application, and the establishment of international collaboration for machine learning-based innovation development. Program evaluation also indicated strong sustainability potential through joint research and similar initiatives at the global level. The program concluded that integrating technology into athlete classification processes can improve accuracy, efficiency, and competitive fairness in boccia sport.